Vince Flynn [compact disc, unabridged] : order to kill : a Mitch Rapp novel - Flynn, Vince, 1966-2013; Mills, Kyle, 1966- (Flynn, Vince, 1966-2013. Mitch Rapp novel, 2016)
Mitch Rapp is used to winning. But now the CIA operative finds himself chasing false leads from continent to continent in an effort to keep Pakistani nukes from falling into the hands of terrorists. Together with friend and colleague Scott Coleman, Rapp struggles to prevent the loss of these lethal weapons, particularly because Russia is also interested in the nukes, though not for the same reason as Rapp and Coleman. Soon, it becomes alarmingly clear that the forces in Moscow are bent on fomenting even more chaos and turmoil in the Middle East, and Rapp must go deep into Russian territory, posing as an American ISIS recruit. There, he uncovers a plan much more dangerous and insidious than he ever expected, one that could have far-reaching and catastrophic consequences.